Hubungan Homesickness dengan Kesehatan Mental Mahasiswa Perantau : Studi Literatur - Putri Rahayu; Silva Anugrah Febrina; Wita Dwi Anjani; Sri Mulyeni (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Migrant students often face significant emotional challenges when transitioning to a new academic and living environment. One prominent issue is homesickness, which can disrupt emotional balance and impact overall mental health. In this context, homesickness is not only associated with feelings of longing for home and family but also affects psychological stability and the ability to adapt to new environments. This article aims to synthesize research findings on the relationship between homesickness and mental health among migrant students, with a focus on the higher education context in Indonesia. A literature review was conducted by searching Google Scholar, Garuda, DOAJ, and ERIC using the keywords